1987
DOI: 10.1002/cbf.290050404
|View full text |Cite
|
Sign up to set email alerts
|

Δ53β hydroxysteroid dehydrogenase activity of the rat corpus luteum exhibits positive substrate‐binding co‐operativity: A continuous monitoring microdensitometric study with unfixed ovarian tissue sections

Abstract: delta (5)3 beta hydroxysteroid dehydrogenase activity transforms biologically inactive delta (5)3 beta hydroxy steroids into the active delta (4)3-keto products (e.g. pregnenolone to progesterone). Using a cytochemical procedure which allows for the continuous microdensitometric monitoring of an enzyme reaction as it proceeds and a well described cytochemical assay for delta (5)3 beta HSD we have analysed the initial velocity rates (Vo) for dehydroepiandrosterone (DHEA) binding to this enzyme in regressing (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recent evidence has indicated that 3ß-HSD activity is the second major ratelimiting step (after cholesterol ester cleavage) in the production of testosterone by Leydig cells (Lambert et al 1986). Moreover, kinetic studies on the rat ovarian corpora lutea have revealed that the enzyme exhibits positive co-operative substrate binding, an indication of an enzyme under regulatory control (Gordon & Robertson, 1987). It has been established that steroid¬ ogenic enzymes, including 3ß-HSD, are inducible in steroid-producing cells by the trophic action of pituitary hormones (Ewing & Zirkin, 1983).…”
Section: Discussionmentioning
confidence: 98%
“…Recent evidence has indicated that 3ß-HSD activity is the second major ratelimiting step (after cholesterol ester cleavage) in the production of testosterone by Leydig cells (Lambert et al 1986). Moreover, kinetic studies on the rat ovarian corpora lutea have revealed that the enzyme exhibits positive co-operative substrate binding, an indication of an enzyme under regulatory control (Gordon & Robertson, 1987). It has been established that steroid¬ ogenic enzymes, including 3ß-HSD, are inducible in steroid-producing cells by the trophic action of pituitary hormones (Ewing & Zirkin, 1983).…”
Section: Discussionmentioning
confidence: 98%
“…The use of the M85A microdensitometer for computerized continuous monitoring has been described previously (Robertson et al, 1984;Gordon & Robertson, 1986, 1987.…”
Section: The M85a Systemmentioning
confidence: 99%
“…In particular methods have been developed for the continuous monitoring of enzyme activity in tissue sections (Kugler, 1981;Robertson et al, 1984). Such techniques allow measurements at a large number of time points to be made as the reaction proceeds and we have described such a method in detail for the monitoring of the activity of ovarian 36-hydroxysteroid dehydrogenase using the Vickers M85A microdensitometer and Commodore PET microcomputer (Robertson et al, 1984;Gordon & Robertson, 1986, 1987.…”
Section: Introductionmentioning
confidence: 99%